PENGARUH PAD, DAU, DBH DAN BELANJA MODAL TERHADAP PDRB DAN KEMISKINAN DI KABUPATEN JOMBANG - Verlandes, Yuliasnita; Isnaini, Nurdiana Fitri; Nersiwad, Nersiwad; Purnomo, Agoes Hadi (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to analyze the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), Revenue Sharing Fund (DBH), and capital expenditure on economic growth and poverty level in Jombang Regency during the 2014-2020 period. Using multiple linear regression analysis methods with secondary data from the Central Statistics Agency (BPS) and the Directorate General of Financial Balance (DJPK), this study found that simultaneously, the variables PAD, DAU, DBH, and capital expenditure did not have a significant effect on GDP and poverty levels. However, partially, PAD has been shown to have a significant positive influence on economic growth, while DAU, DBH, and capital expenditure do not show a significant influence. For poverty levels, the results show that no independent variables have a significant effect, although PAD, DBH, and capital expenditure tend to reduce poverty rates. This study suggests that the Jombang local government optimize PAD and the use of budgets for programs that have a direct impact on the community to increase economic growth and reduce poverty